Synthesis of 1-amidoalkyl-2-naphthols based on a three-component reaction catalyzed by boric acid as a solid heterogeneous catalyst under solvent-free conditions - Zahed Karimi-Jaberi; Hadi Fakhraei (Bulletin of the Chemical Society of Ethiopia, 2012)
An efficient method for the preparation of 1-amidoalkyl-2-naphthols has been described using a multi-component, one-pot condensation reaction of 2-naphthol, aldehydes and amides in the presence of boric acid under solvent-free conditions.DOI: http://dx.doi.org/10.4314/bcse.v26i3.18